MENINGKATKAN DAN MENUMBUHKAN MINAT BAKAT SISWA SDN2 BERINGKIT BELAYU DALAM MENULIS MENGGUNAKAN METODE PEMBELAJARAN - I Gusti Ayu Putu Tuti Indrawati; Ni Luh Sukanadi; Gusti Agung Mirah Anggreni Raka (JURNAL PENGABDIAN MANDIRI, 2024)
Education is one of the most fundamental needs for humans. It helps individuals improve by enhancing their skills as they learn new things. Many lessons can be taught to the people of Indonesia, from basic education to higher education levels (Tamrin & Yanti, 2019). In the Indonesian language, four skills must be mastered: listening, speaking, reading, and writing. These skills can be categorized into two activities: productive and receptive. Reading and writing are considered productive activities while listening and speaking are receptive activities. In Beringkit BelayuIndonesian Village, there are two elementary schools: SDN 2 Beringkit Belayu and SDN 2 Beringkit Belayu. The authors conducted teaching activities at SDN 2 Beringkit Belayu during this community service activity. Based on our observations at the school, we found that some students have certain skill deficiencies. Specifically, some students struggle with reading and writing, as well as one student who has difficulty focusing and paying attention during lessons. To address these issues, we implemented a teaching method aimed at enhancing and nurturing the student's interests and talents in writing. This community service activity is expected to help students who are facing these challenges. We hope that it will not only improve their skills but also change their perspective on learning, leading to better focus and direction in their studies